Urinary and serum biomarkers for the diagnosis of acute kidney injury: an in-depth review of the literature - Vanmassenhove, Jill; Vanholder, Raymond; Nagler, Evi; Van Biesen, Wim (Nephrology, dialysis, transplantation, 2013)
Acute kidney injury (AKI) remains associated with high morbidity and mortality, despite progress in medical care. Although the RIFLE (Risk, Injury, Failure, Loss, End-Stage Kidney Disease) and AKIN (Acute Kidney Injury Network) criteria, based on serum creatinine and urine output, were a step forward in diagnosing AKI, a reliable tool to differentiate between true parenchymal and pre-renal azotaemia in clinical practice is still lacking. In the last decade, many papers on the use of new urinary and serum biomarkers for the diagnosis and prognostication of AKI have been published. Thus, the question arises which biomarker is a reliable differential diagnostic tool under which circumstances. We searched Medline from inception to April 2012 using medical subject heading and text words for AKI and biomarkers [neutrophil gelatinase-associated lipocalin (NGAL), kidney injury molecule-1 (KIM-1), Cystatin C, interleukin-6 (IL-6), interleukin-8 (IL-8), interleukin-18 (IL-18), N-acetyl-glucosaminidase (NAG), glutathione transferases (GST) and liver fatty acid binding protein (LFABP)] to identify relevant papers in five different settings (paediatrics, cardiac surgery, emergency department, critically ill and contrast-induced nephropathy). We included 87 relevant papers, reporting on 74 studies. Depending upon the setting, 7-27 different definitions of AKI were used. Reported diagnostic performance of the different biomarkers was variable from poor to excellent, and no consistent generalizable conclusions can be drawn on their diagnostic value. Early diagnosing of AKI in clinical conditions by using new serum and urinary biomarkers remains cumbersome, especially in those settings where timing and aetiology of AKI are not well defined. Putting too much emphasis on markers that have not convincingly proven reliability might lead to incorrect interpretation of clinical trials. Further research in this field is warranted before biomarkers can be introduced in clinical practice.